Community Perceptions of Adaptation and Mitigation Practices for Tidal Flooding in West Banjarmasin District, Banjarmasin City, Indonesia - Languyu, Erika Christine; Nasruddin, Nasruddin (Geosfera Indonesia, 2026)
Banjarmasin is a lowland area with an average elevation of 1.23 meters above sea level, making it highly vulnerable to flooding. This study aims to analyze community adaptation and mitigation strategies in response to tidal flooding in the West Banjarmasin Subdistrict, Banjarmasin City. The research employed a quantitative, descriptive approach, using interviews with 100 household heads from nine urban villages. The findings indicate that community adaptation was categorized as high (93.7%), moderate (5.7%), and low (0.7%). Among the assessed parameters, preparedness for flood events obtained the lowest score (79%) compared to other adaptation indicators. Meanwhile, the level of community mitigation was categorized as high (91.2%), moderate (8.5%), and low (0.3%). Weather condition monitoring was identified as the lowest-scoring parameter (68%) among the mitigation indicators. These findings suggest that the Banjarmasin City Government should actively engage in public awareness and outreach programs, particularly to strengthen community preparedness for flooding. Furthermore, more serious and systematic measures are required to improve tidal flood mitigation, especially regarding weather monitoring